Ginsenoside Rd protects against acute liver injury by regulating the autophagy NLRP3 inflammasome pathway - Xiaomei Zhong; Yibin Sun; Yanxiang Lin; Shan Deng; Huan Wang; Xian Zhou; Jinjian Lu; Yanfang Zheng; Ruoyin Luo; Mingqing Huang; Jianyuan Song (Scientific Reports)
Abstract Ginsenoside Rd (Rd) is a bioactive compound predominantly found in Panax ginseng C.A. Meyer and Panax notoginseng (Burkill) F.H. Chen ex C.H. Chow, both species belonging to genus Panax in the Araliaceae family. However, its hepatic protective effect against acute liver injury and related mechanistic action remain unexplored. To investigate the protective effect of Rd against thioacetamide (TAA)-induced acute liver injury and assess its underlying regulatory mechanisms related to autophagy and inflammation. Forty-eight 8 weeks old C57BL/6 mice were treated with saline (control or model group), Rd (12.5 mg/kg, 25 mg/kg or 50 mg/kg), and diammonium glycyrrhizinate (DG, 30 mg/kg) for three days. Then the mice were stimulated with TAA to establish acute liver injury model, excluding the control group. HSC-T6 cells were treated with Rd at concentrations of 2.5, 5, or 10 µM, for 12 h with or without Lipopolysaccharide (LPS) stimulation at 100 ng/mL. Immunofluorescence staining, qPCR and Western blot were employed to analyze the expressions of genes and proteins associated with inflammation and autophagy. To validate the role of Rd in regulating autophagy and inflammation, the autophagy inducers, rapamycin and GSK621, were utilised in reverse validation experiments in cells. Rd exhibited significant hepatic protective effects in mice by reducing the serum levels of Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Glutathione S-transferase (GST) and Lactate dehydrogenase (LDH) with acute liver injury. It exhibited strong anti-inflammatory effect by reducing inflammation associated protein, such as cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), nod-like receptor protein 3 (NLRP3), associated speck-like protein containing a CARD (ASC), interleukin-18 (IL-18) and interleukin-1β(IL-1β) proteins and the mRNA expression levels of COX-2, Tumor Necrosis Factor α (TNF α), interleukin-6 (IL-6) and iNOS were decreased in liver tissue. And Rd inhibited LPS-induced inflammation by reducing the expression of COX-2 and NLRP3 in HSC-T6 cells. Moreover, not only in vivo but also in vitro, Rd downregulated the expression of LC3II, Beclin1, phosphorylation-AMP-activated protein kinase (p-AMPK), phosphorylation-ULK1 (p-ULK1) and upregulated the expression of p62 and phosphorylation-mechanistic target of rapamycin (p-mTOR) to suppress autophagy via the AMPK/mTOR/ULK1 pathway. Finally, the inhibitory effects of Rd on autophagy and inflammation in HSC-T6 cells were partially blocked by rapamycin and GSK621. Rd is a promising therapeutic agent to protect liver against TAA-induced acute liver injury by regulating the autophagy-NLRP3 inflammasome pathway.